Analysis of aroma and yield components of aromatic rice in Malaysian tropical environment - Golam, Faruq; Yeap, Hui Yin; Abrar, Masitah; , Nur Afnierna; Abdul Majid, Nazia; Khalid, Norzulaani; Osman, Mohamad (Southern Cross Journals, 2011)
Low yield is a common phenomenon of aromatic rice and consequently rice breeders are trying to develop the agronomic characters to gain a better grain yield. In this study, a total of 53 rice genotypes including 12 globally popular aromatic rice cultivars and 39 advanced breeding lines were evaluated for yield and yield contributing characters in Malaysian tropical environment. Two local varieties MRQ 50 and MRQ 72 were used as check varieties. Correlation analysis revealed that the number of fertile tillers (r = 0.69), grain/panicle (r = 0.86) and fertile grain per panicle (r = 0.65) have the positive contribution to grain yield. Highest grain yield was observed in E36, followed by Khau Dau Mali, E26 and E13. E36 appeared with lowest plant height and it also produced highest number of fertile tillers. After evaluation of yield components four genotypes namely E36, Khau Dau Mali, E26 and E13 were selected as outstanding genotypes, which can be used as potential breeding materials for Malaysian tropical environment. Keywords: Aromatic rice, Yield, Yield component, Tropical environment